Recent Advances in Natural Products Chemistry Related to Metabolites and Microbiomes - Vinale, Francesco; Balestrieri, Maria Luisa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue is dedicated to recent advances in natural products chemistry related to metabolites and microbiomes. In the present Special Issue, the following topics have been covered: • Isolation of novel microbial compounds using metabolomic approaches; • Molecules and metabolomes related to agricultural applications (crop and animal productions); • Microbiomes and related natural products with beneficial effects in agriculture; • Plant metabolites with bioactive properties; • Influence of beneficial microbes and/or their metabolites on plant metabolomes; • Microbial metabolites involved in plant or animal interactions; • Influence of production technologies on animal metabolomes and microbiomes.